SIRT6 Promotes Osteogenic Differentiation of Adipose-Derived Mesenchymal Stem Cells Through Antagonizing DNMT1 - Bo Jia; Bo Jia; Jun Chen; Qin Wang; Xiang Sun; Jiusong Han; Fernando Guastaldi; Shijian Xiang; Qingsong Ye; Qingsong Ye; Yan He (Frontiers in Cell and Developmental Biology, 2021)
BackgroundAdipose-derived stem cells (ADSCs) are increasingly used in regenerative medicine because of their potential to differentiate into multiple cell types, including osteogenic lineages. Sirtuin protein 6 (SIRT6) is a nicotinamide adenine dinucleotide (NAD)-dependent deacetylase that plays important roles in cell differentiation. NOTCH signaling has also been reported to involve in osteogenic differentiation. However, the function of SIRT6 in osteogenic differentiation of ADSCs and its relation to the NOTCH signaling pathways are yet to be explored.MethodsThe in vitro study with human ADSCs (hADSCs) and in vivo experiments with nude mice have been performed. Alkaline phosphatase (ALP) assays and ALP staining were used to detect osteogenic activity. Alizarin Red staining was performed to detect calcium deposition induced by osteogenic differentiation of ADSCs. Western blot, RT-qPCR, luciferase reporter assay, and co-immunoprecipitation assay were applied to explore the relationship between of SIRT6, DNA methyltransferases (DNMTs) and NOTCHs.ResultsSIRT6 promoted ALP activity, enhanced mineralization and upregulated expression of osteogenic-related genes of hADSCs in vitro and in vivo. Further mechanistic studies showed that SIRT6 deacetylated DNMT1, leading to its unstability at protein level. The decreased expression of DNMT1 prevented the abnormal DNA methylation of NOTCH1 and NOTCH2, resulting in the upregulation of their transcription. SIRT6 overexpression partially suppressed the abnormal DNA methylation of NOTCH1 and NOTCH2 by antagonizing DNMT1, leading to an increased capacity of ADSCs for their osteogenic differentiation.ConclusionThis study demonstrates that SIRT6 physical interacts with the DNMT1 protein, deacetylating and destabilizing DNMT1 protein, leading to the activation of NOTCH1 and NOTCH2, Which in turn promotes the osteogenic differentiation of ADSCs.